A teaching model impact of learning outcomes for mathematical content in functions - A.S.Tabieh, Ahmad (Opción, 2020)
This study aims at measuring the effectiveness of a teaching model based on learning outcomes according to the system approach in helping students acquire the standards for mathematical content in functions.The study was applied to two hundred students of eight sections which were randomly divided into two groups: control and experimental. The first instrument was a pre-test designed to determine the comparability of the two groups’ performance in the prerequisites. The second was a post-test, investigating the effectiveness of the model after treatment. It was discovered that the model significantly improved the students’ performance in interpreting functions, building functions, and polynomial models